Probing the weak limit of magnetocrystalline anisotropy through a spin‒flop transition in the van der Waals antiferromagnet CrPS4 - Jae Yeon Seo; Sunghyun Lim; Hyun Jun Shin; Ki Won Jeong; Jae Min Hong; Kyungsun Moon; Mi Kyung Kim; Nara Lee; Young Jai Choi (NPG Asia Materials)
Abstract The influence of magnetocrystalline anisotropy (MCA) on antiferromagnetism is elucidated through the characterization of the spin‒flop transition. However, due to a lack of suitable candidates for investigation, a detailed understanding of the preservation of the spin‒flop transition in the presence of low MCA energy remains elusive. In this study, we introduce CrPS4, which is a two-dimensional van der Waals antiferromagnet, as an ideal system to explore the exceedingly weak limit of the thermally-evolved MCA energy. By employing a uniaxially anisotropic spin model and fitting it to the experimental magnetic properties, we quantify the MCA energy and identify the discernible spin configurations in different magnetic phases. Notably, even at the limit of extremely weak MCA, with a mere 0.12% of the interlayer antiferromagnetic exchange interaction at T = 33 K, which is slightly below the Néel temperature (T N) of 38 K, the spin‒flop transition remains intact. We further establish a direct correlation between the visualized spin arrangements and the progressive reversal of magnetic torque induced by rotating magnetic fields. This analysis reveals the essential role of MCA in antiferromagnetism, thus extending our understanding to previously undetected limits and providing valuable insights for the development of spin-processing functionalities based on van der Waals magnets.